Overview of the Level of Knowledge of Adolescent Girls About Personal Hygiene in Preventing Pathological Leukorrhea at Limboto 1 Public Middle School - Dwi Putri Adinda Kaharu; Nurdiana Djamaluddin; Ibrahim Suleman (Universitas Muhammadiyah Palu, 2026)
Adolescence is a phase that is prone to reproductive health problems, one of which is pathological leukorrhea which is closely related to personal hygiene behavior. The level of knowledge is a determining factor in the formation of these behaviors. This study aims to determine the level of knowledge of adolescent girls about personal hygiene in the prevention of pathological leukorrhea at SMP Negeri 1 Limboto. This study uses a non-experimental quantitative design with a descriptive method. The population amounted to 258 female students with a sample of 157 respondents who were selected using proportional random sampling techniques. The research instrument is in the form of a knowledge questionnaire consisting of 30 statement items with a Guttman scale. Data were analyzed using univariate analysis. The results showed that most of the young women had a good level of knowledge, namely 136 respondents (86.6%), followed by 20 respondents (12.7%) with sufficient knowledge, and 1 respondent (0.6%) with insufficient knowledge. In conclusion, the majority of adolescent girls already have good knowledge of personal hygiene in the prevention of pathological leukorrhea. Nevertheless, there are still a small percentage of young women with sufficient and insufficient knowledge. Therefore, it is recommended that schools and health workers improve structured and sustainable reproductive health education programs.